Citric Acid and the RNA World1. Issue 21 (19th May 2014) - Müller, Ulrich F.; Tor, Yitzhak
<x xml:space="preserve">Abstract</x> RNA world: The chelation of magnesium ions by citric acid prevents the magnesium‐induced aggregation of lipid vesicles and RNA degradation while promoting nonenzymatic RNA oligomerization. These findings suggest a unique role for this simple organic acid in supporting key processes in RNA world organisms.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>